Zymosan attenuates melanoma growth progression, increases splenocyte proliferation and induces TLR-2/4 and TNF-α expression in mice - Mehdi Taghavi; Esmaeil Mortaz; Alireza Khosravi; Ghasem Vahedi; Gert Folkerts; Mohammad Varahram; Mehdi Kazempour-Dizaji; Johan Garssen; Ian M. Adcock (BMC, 2018)
Abstract Background Melanoma is one of the most common types of skin malignancies. Since current therapies are suboptimal, considerable interest has focused on novel natural-based treatments. Toll-like receptors (TLRs) play an important role in evoking innate immunity against cancer cells. Zymosan, a known TLR-2 agonist, is a glucan derived from yeast cell walls with promising immunomodulatory effects. The aim of this study was to evaluate whether Saccharomyces cerevisiae-derived zymosan-modulated skin melanoma progression by regulation of TLR-2 and TLR-4 expression in peritoneal macrophages and serum TNF-α level. Methods Male C57BL/6 mice were divided into four groups: i) zymosan-treated (Z), ii) Melanoma-bearing mice (M), iii) Melanoma-bearing mice treated with zymosan (ZM) and iv) a healthy control group (negative control). 15 days after melanoma induction, mice were injected i.p. with zymosan (10 μg) daily for 4 consecutive days. Mice were CO2-euthanized and serum TNF-α level, TLR-2 and TLR-4 expression in peritoneal macrophages and tumor growth measured. Splenocytes were treated ex-vivo with zymosan to determine viability and proliferation. Results Tumor weight significantly decreased following therapeutic dosing with zymosan (P < 0.05). This was associated with zymosan-induced upregulation of TLR-2, TLR-4 and TNF-α mRNA in peritoneal macrophages and enhanced serum TNF-α levels (P < 0.05). Splenocyte number and viability were increased in a concentration-dependent manner by zymosan. Conclusions Our study suggests that zymosan-induced upregulation of TLR-2, TLR-4 and TNF-α gene expression and of TNF-α release; together with increased level of lymphocyte proliferation may play a role in the inhibition of melanoma progression.